2017
DOI: 10.1161/circep.117.005273
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Arrhythmia Recurrence After Hybrid Epi- and Endocardial Radiofrequency Ablation for Persistent Atrial Fibrillation

Abstract: Background-Long-term efficacy of catheter-based treatment of persistent atrial fibrillation is unsatisfactory. Minimally invasive surgical ablation techniques have been developed recently, but their efficacy has never been systematically tested. Methods and Results-Seventy patients (median age, 63.5 years) with persistent atrial fibrillation underwent epicardial thoracoscopic radiofrequency pulmonary vein isolation, linear ablation, Marshal ligament disruption, and exclusion of the left atrial appendage. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
3
10
0
1
Order By: Relevance
“…Our study (1) and others (9,10) have clearly showed that complete transmural lesions in the left atrium cannot be obtained, in the majority of (let alone all) patients, after an epicardial ablation alone (using bipolar RF energy). The worst outcomes are more associated with left atrial linear lesions compared to PV isolations.…”
Section: Timing Of the Staged Catheter Ablation In Hybrid Proceduressupporting
confidence: 56%
See 1 more Smart Citation
“…Our study (1) and others (9,10) have clearly showed that complete transmural lesions in the left atrium cannot be obtained, in the majority of (let alone all) patients, after an epicardial ablation alone (using bipolar RF energy). The worst outcomes are more associated with left atrial linear lesions compared to PV isolations.…”
Section: Timing Of the Staged Catheter Ablation In Hybrid Proceduressupporting
confidence: 56%
“…If we adopt the paradigm that durable PV isolation is the major factor precluding arrhythmia recurrence during longterm follow-up of patients after epicardial RF ablation, then based on our results, we should draw the conclusion that omitting endocardial catheter ablation after surgery would result in at least a 30% arrhythmia recurrence rate, which corresponds to the PV reconnection rate seen in our study (1). Extending this assumption to linear lesions (box lesion, trigone line) would lead to an arrhythmia recurrence rate of at least 70%.…”
mentioning
confidence: 72%
“…It could raise a question whether endocardial ablation of certain lines, including cavo-tricuspid-isthmus, is necessary before the window period. Accordingly, we changed the timing of endocardial procedure from an early stage (5 days after surgery) to three months after the surgery (window period), in line with a previously published paper (15). However, we perform staged hybrid procedure in patients with atrial tachyarrhythmia only despite epicardial ablation.…”
Section: Rationale and Timing Of Endocardial Electrophysiological Conmentioning
confidence: 99%
“…We read the paper of Bulava et al regarding the correlation of arrhythmia recurrence after hybrid epicardial and endocardial radiofrequency ablation for persistent atrial fibrillation with great interest (15). We would like to discuss the results regarding: (I) safety of thoracoscopic epicardial ablation; (II) timing of post-procedural endocardial electrophysiological confirmation; (III) recurrent atrial tachyarrhythmia after epicardial thoracoscopic ablation.…”
mentioning
confidence: 99%
“…In a study published last year, 21 70 patients with persistent AF underwent minimally invasive epicardial surgery for AF followed by catheter-based electroanatomic mapping and ablation 2 to 3 months later. The majority of patients after epicardial ablation were found to require additional endocardial catheter ablation to complete the ablation sets.…”
Section: Surgical and Hybrid Af Ablationmentioning
confidence: 99%